How Financial Literacy and Lifestyle Shape Financial Behavior in Using Paylater Service (Case Study of Students in UNISNU Jepara) - Wintana, Hetty; jumaiyah, jumaiyah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
Buy now pay later (BNPL) services in banking are increasingly popular among Indonesians. Studies show that a good understanding of finances is essential for financial decision-making. There are not many studies that discuss how students use paylater services. There is not much research on how the relationship between financial literacy and lifestyle can affect paylater usage behavior. This quantitative research involved 394 active students at the Nahdlatul Ulama Islamic University (UNISNU) Jepara, who were selected by purposive sampling method. Data was collected using questionnaire tools that were disseminated through Google Forms. Partial Least Squares Structural Equation Modeling (PLS-SEM), assisted by Smart-PLS 4.0 software, is used to analyze the data. The results show that lifestyle and the use of paylater services positively and significantly affect students' financial behavior. However, this study shows that the financial literacy of UNISNU Jepara students does not have a significant influence on their financial behavior; On the other hand, lifestyle and the use of payment services have a significant effect. It shows that more than just financial literacy, consumption patterns, and ease of access to financial technology influence financial behavior. This study will help educational institutions and financial service providers to place more emphasis on developing healthy financial habits as well as help students become more responsible and better at making financial decisions